The facial profile in brazilian adults - Taísa Figueiredo Chagas; Mariana Martins e Martins; José Nelson Mucha (Universidade Estadual de Campinas, 2017)
AIM: To investigate if there is agreement between measurement values obtained for Brazilian adults and the values recommended by Holdaway, Merrifield, Burstone, Steiner and Ricketts, for facial profile soft tissue analysis. METHODS: A sample of 30 cephalometric radiographs was used, consisting of 15 women and 15 men, aged 18 to 31 years, all exhibiting excellent occlusion and balanced facial profile. Comparisons were made with the measurement values proposed by the aforementioned authors using Student's t-test and to determine the correlation between the ANB and Â-H measurement values described by Holdaway, using Pearson's correlation coefficient. RESULTS: Among the measures evaluated, 4 showed statistically significant differences: Â.Z (Merrifield), S-LS and S-LI (Steiner), and E-LI (Ricketts) relative to the standards recommended by the authors. The measurement values advocated by Merrifield, Steiner and Ricketts showed statistical differences, and as for the Z-angle, Brazilians feature a slightly more convex profile, which appeared slightly concave according to Steiner, and according to the E-Plane (Ricketts), it meant an increased protrusion of the lower lip. CONCLUSION: It could be asserted that adult Brazilians have a slightly more convex facial profile than US standards, but these differences should be viewed with caution, as they are clinically unimportant.